Importance of selenium in human nutrition - Combs, Jr.,Gerald F (MTT, 2005)
In the span of five decades, Se has moved from being thought of as a toxicant to being considered essential nutrient. The elucidation of its role in nutrition has led to fundamental discoveries in metabolic biochemistry (the unique metabolism of SeCys), virology (the destabilization of RNA viruses due to oxidative stress), and public health (the role in cancer risk reduction). Unlike most other nutrients, which were recognized due to the fatal outcomes of their deficiencies, the consequences of Se deprivation appear to be largely sub-clinical in nature, requiring other precipitating factors (e.g., vitamin E deficiency, viral exposure, etc.) to reveal the effects of compromised Se-enzymes and/or essential Se-metabolites. Even after a half-century of research, much remains to learn about the metabolic bases of the roles of Se in nutrition and health.
Keywords: Ka; selenium; nutrition; food; diet; intake; plasma; selenium deficiency